ISSUES OF DEVELOPMENT OF THE COUNTRY’S ECONOMY BASED ON THE CONCEPT OF GREEN ECONOMY - Haydarova Dildora Jahongir kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article is devoted to the study of the potential and problems of implementing the concept of green economy in Uzbekistan. The main aspects of the green economy, its importance for the sustainable development of the country and the ecosystem, as well as methods for integrating green technologies into key sectors of the economy are considered. The article presents data on the current state of the environment in Uzbekistan, as well as analyzes the main challenges and opportunities for the country’s transition to a sustainable economy. The focus is on energy efficiency, water resources protection and the development of green technologies, as well as the role of public and private initiatives in the implementation of the green economic strategy.